2006
DOI: 10.1101/gr.5680406
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally high levels of recombination across the honey bee genome

Abstract: The first draft of the honey bee genome sequence and improved genetic maps are utilized to analyze a genome displaying 10 times higher levels of recombination (19 cM/Mb) than previously analyzed genomes of higher eukaryotes. The exceptionally high recombination rate is distributed genome-wide, but varies by two orders of magnitude. Analysis of chromosome, sequence, and gene parameters with respect to recombination showed that local recombination rate is associated with distance to the telomere, GC content, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
200
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(227 citation statements)
references
References 44 publications
23
200
3
1
Order By: Relevance
“…This analysis demonstrates that the socially advanced honeybee A. mellifera and the ants studied to date (all of which are socially advanced) are characterized by unusually high recombination densities. For the honeybee, Beye et al (2006) have shown that this high recombination density is a genome-wide phenomenon, although there is large local variation. The authors particularly showed that whereas there are weak positive correlations with GC-content and repetitive DNA, recombination densities are not influenced by chromosome size.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis demonstrates that the socially advanced honeybee A. mellifera and the ants studied to date (all of which are socially advanced) are characterized by unusually high recombination densities. For the honeybee, Beye et al (2006) have shown that this high recombination density is a genome-wide phenomenon, although there is large local variation. The authors particularly showed that whereas there are weak positive correlations with GC-content and repetitive DNA, recombination densities are not influenced by chromosome size.…”
Section: Discussionmentioning
confidence: 99%
“…Watterson's estimator of the population mutation rate per base (θ w ) in African bees was 0.79%, whereas native European subspecies had lower levels of variation (average θ w values of 0.30% and 0.33% for the C and M groups, respectively), and Middle-Eastern subspecies were intermediate (average θ w value of 0.47%; Table 1 and Supplementary Note), in concordance with previous studies based on a few loci 16 . We also note an extremely fast decay of linkage disequilibrium (LD) with physical distance, which reflects the high recombination rate in honeybees 18 (~50% reduction in the r 2 linkage statistic with only 500 bp; Supplementary Fig. 4).…”
mentioning
confidence: 81%
“…Specifically, for each chromosome, we created a function relating recombination distance to physical distance using a least squares fit of a six-term polynomial of physical distance to recombination distance; R 2 . 0.99 for all chromosomes (Beye et al 2006;Solignac et al 2007). After estimating QTL position, QTL allele frequencies were estimated and used to estimate QTL substitution effects, a i , for each mapping population (following Dekkers 2000; Wang et al 2007).…”
Section: Methodsmentioning
confidence: 99%